1982
DOI: 10.1007/bf00231411
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative retinal fibrosis — a controlled clinical study of systemic steroid therapy

Abstract: In a prospective clinical trial, the effect of systemic steroids on the incidence and severity of retinal fibrosis following retinal detachment surgery was tested against placebo. Several grades of retinal fibrosis of various degrees of severity were defined prior to the study. The maximum postoperative incidence of eyes with any signs of retinal fibrosis was 65% (75.4% in the placebo group, 63.3% in the steroid group). A set of fibrosis criteria was identified that had a tendency to respond to systemic steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 8 publications
0
34
0
3
Order By: Relevance
“…Besides their use in conditions such as proliferative diabetic retinopathy, 20 diabetic macular edema, 6 exudative AMD, 7 or central retinal vein occlusion, 21 steroids have also been applied in combination with intraocular surgery. Kö rner et al 22 reported a trend to a reduction of postoperative fibrosis after systemic cortisone therapy. Valone et al 23 report in their study about 134 patients with complete retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their use in conditions such as proliferative diabetic retinopathy, 20 diabetic macular edema, 6 exudative AMD, 7 or central retinal vein occlusion, 21 steroids have also been applied in combination with intraocular surgery. Kö rner et al 22 reported a trend to a reduction of postoperative fibrosis after systemic cortisone therapy. Valone et al 23 report in their study about 134 patients with complete retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of posttraumatic retinal detachments in the cell injection model of PVR after treatment with intraocular triamcinolone has been reported recently [7]. In a prospective clinical study prednisone reduced the postoperative incidence of light signs of fibrosis whereas advanced cases of PVR were not significantly influenced by systemic steroid therapy [14]. However, the oral application of prednisone was only initiated on the fifth postoperative day while the experimental study [7] evaluated the intraocular application of triamcinolone as a pretreatment given one day preoperatively as a bolus.…”
Section: Discussionmentioning
confidence: 99%
“…85 The degree of ERM formation was graded pre and postoperatively and patients randomly allocated to steroid or placebo. The treatment group received 100 mg Prednisolone daily for five days starting on the fifth post-operative day with reducing doses thereafter for 40 days.…”
Section: Anti-inflammatory Agents In Experimentalmentioning
confidence: 99%